A Clinical Research Study of Cognitive Dysfunction and Affective Impairment after Isolated Brainstem Stroke - Fu, Xiujuan; Lu, Zuneng; Wang, Yan; Huang, Lifang; Wang, Xi; Zhang, Hong; Xiao, Zheman (Frontiers in Aging Neuroscience, 2017)
Although the function of cerebellum in neurocognition is documented, the similar role of brainstem is underexplored. This clinical research aims to combine available neuropsychological assessments and P300 to explore the cognitive dysfunction and affective impairment after brainstem stroke. 34 patients with isolated brainstem stroke and 26 health controls were participated in this experiment. The participants accepted the assessment of P300, ACE-III, MoCA, TMT, SDMT, DS, Stroop test and SAS, SDS. Statistical analysis was carried out on the two groups of participants. The results revealed that brainstem stroke caused mild cognitive impairment (MCI), and that visuospatial, executive, attention, linguistic and emotional disturbances may occur after isolated brainstem stroke. Cognitive decline was linked to the P300 latency, ACE-III and MoCA, and P300 latency was correlated with ACE-III. The patients with right brainstem lesions were more likely to suffer memory decline.